RANCANG BANGUN APLIKASI PENCATATAN DATA KEPENDUDUKAN KELURAHAN PAHLAWAN BERBASIS WEB - Ali Ibrahim; Ahmad Rifai; Lina Oktarina (Jurnal Sistem Informasi, 2016)
AbstractKelurahan pahlawan the activities are still using manual systems in the process ofrecording data so that the population data recording process, searching and reporting ofdata becomes less effective. Residents recording is a routine activity for governmentrelatedengineering science, collecting, recording, population data that consists of datamoved, the data entrants, date of birth, mortality data, and the card families. PopulationData Listing of Applications In kelurahan pahlawan is designed to facilitate the recordingof data and preparing reports efficiently and effectively. This application is built with thenotation Flowchart, Data Flow Diagram, Entity Relationship Diagram and programmingis PHP and MySql as DBMS, method development and modeling systems engineering,requirements analysis, design, coding, testing and maintenance. Population Datamutilations application has several advantages, such as to show the number of people inthe kelurahan pahlawan of every month.Keywords: Population Data Recording, PHP, MySql, DatabaseÂ AbstrakKelurahan pahlawan dalam kegiatannya masih menggunakan system manualdalam proses pencatatan data penduduk sehingga proses pencatatan data, pencarian danpelaporan data menjadi kurang efektif. Pencatatan Penduduk merupakan kegiatan yangrutin dilakukan pemerintah untuk ilmu yang berhubungan dengan teknik, pengumpulan,mencatat, data penduduk yang terdiri dari data pindah, data pendatang, data kelahiran,data kematian. Aplikasi Pencatatan Data Kependudukan Pada KelurahanPahlawan ini dirancang sedemikian rupa untuk mempermudah dalam pencatatan data danpembuatan laporan secara efisien dan efektif. Aplikasi ini dibangun dengan notasiFlowchart, Data Flow Diagram, Entity Relationship Diagram dan pemrograman adalahPHP dan MySql sebagai DBMS, dengan metode pengembangan rekayasa dan pemodelansystem, analisis kebutuhan, desain, pengkodean, pengujian dan pemeliharaan. AplikasiPencacatan Data Kependudukan memiliki beberapa kelebihan, diantaranya adalah dapatmenampilkan jumlah penduduk di kelurahan pahlawan dari setiap bulan.Kata kunci : Pencatatan Data Kependudukan, PHP,MySql, Basis Data